2011
DOI: 10.1007/2288-6729-5-1-55
|View full text |Cite
|
Sign up to set email alerts
|

The Early Childhood Education Workforce in Europe Between Divergencies and Emergencies

Abstract: Across and beyond Europe, demographic, social and economic pressures both at the macro and the micro level are impacting on the work contexts of early childhood educators. Alongside heightened drives towards expansion and increasing regulation of the field, expectations are intensifying. Additionally, goals and targets for higher education and vocational education at the European policy level are generating restructurings of the national qualification systems for work in the early childhood field. In this dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 10 publications
0
12
0
4
Order By: Relevance
“…The problem of preschool teachers' professional training in some European Union countries was covered by German scholars (Bauer et al, 2012;Kotthoff & Denk, 2007;Terhart, 2003); French scholars (Dajez, 1994;Bernard, 2015;Fraisse, 2010;Kyvik, 2009); British scholars (Barton, 2003;Furlong, 2005;Terhart, 2003;Whitty et al, 1997). A particular attention should be paid to thorough works (Caena, 2011;Cameron & Moss, 2007;Moss, 2008;Neuman, 2005;Oberhuemer, 2011;Ostinelli, 2009, Gonzalez & Wagenaar, 2003, which provide comprehensive views on professional training of preschool teachers in Europe.…”
Section: Introductionmentioning
confidence: 99%
“…The problem of preschool teachers' professional training in some European Union countries was covered by German scholars (Bauer et al, 2012;Kotthoff & Denk, 2007;Terhart, 2003); French scholars (Dajez, 1994;Bernard, 2015;Fraisse, 2010;Kyvik, 2009); British scholars (Barton, 2003;Furlong, 2005;Terhart, 2003;Whitty et al, 1997). A particular attention should be paid to thorough works (Caena, 2011;Cameron & Moss, 2007;Moss, 2008;Neuman, 2005;Oberhuemer, 2011;Ostinelli, 2009, Gonzalez & Wagenaar, 2003, which provide comprehensive views on professional training of preschool teachers in Europe.…”
Section: Introductionmentioning
confidence: 99%
“…Stakeholders' preference on at least a certificate level of teacher education in Tanzania differed with the practice in foreign countries particularly from the developed world. For instance, Oberhuemer (2011) found that 22 out of 27 developed countries in Europe with an exception of Germany, Austria, the Czech Republic, the Slovak Republic, and Malta set a bachelor degree as a minimum credential for teaching the 3-6 year-old preschool children. The bachelor degree as the prerequisite for teaching in pre-school is common to other countries like USA (Burchinal, Hyson & Zaslow, 2008;Kelley & Camilli, 2007;Saracho & Spodek, 2007;Barnett, 2003;Textor, 1998), in Norway (Strand, 2006), Australia (Fenech et al, 2006), Sweden (Sheridan, 2014), and the United Kingdom (Nutbrown, 2012).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Desde diversos ámbitos se insiste en la necesidad de implantar sistemas integrados de EI para que puedan alcanzarse perfiles profesionales coherentes de alto nivel en toda la etapa (Oberhuemer, 2011), en los que impere el concepto de educación integral y se tengan en consideración tanto el componente asistencial de cuidado como el educativo (Van Laere, Peeters y Vandenbroeck, 2012).…”
Section: Modelos De Ei Y Estructura De La Etapa En Francia Inglaterrunclassified